RECOMMENDATIONS FOR PAIN RELIEF IN LABOR - Valmini, Bruna (Health and Society, 2023)
This investigation is therefore justified by its academic, scientific and social relevance, based on the presentation of the latest updates on the subject in question. Aiming: to present the recommendations evidenced in the literature for pain relief during labor. This research was carried out through an integrative literature review, with an exploratory approach, whose institute was summarized in investigating, through already published articles, relevant information that answered the guiding question. Thus, the searches took place through a survey of data in the scientific bases: LILACS and SCIELO. For analysis of the results, 10 articles were selected. In view of these results, through analysis of scientific evidence, the literature found some important outcomes regarding methods for pain relief during labor. Thus, it can be considered that acupuncture, music therapy, lumbosacral massage, aromatherapy, hot baths, relaxing massages and the use of the Swiss ball stand out among the main methods that health professionals can implement to minimize pain and hours of work. This study found in its results that obstetric professionals should promote the use and acceptance of non-pharmacological methods to reduce pain during labor, reduce labor time and encourage women to participate in the physiological process of childbirth. In this context, hydrotherapy, aromatherapy and music therapy were the most cited recommendations as a therapeutic option, which can decrease adrenaline levels throughout the body, leading to pain relief.